Feasibility of decentralised, task-shifted hepatitis C testing and treatment services in urban Myanmar: implications for scale-up - Margaret Hellard; Alisa Pedrana; Hla Htay; Win Lei Yee; Khin Sanda Aung; Jessica Howell; Nwe Nwe; Philippa Easterbrook; Jessica Markby; Sonjelle Shilton; Bridget Louise Draper; Anna Bowring; et al. (BMJ Open)
Objectives To assess the feasibility considerations for a decentralised, one-stop-shop model of care implemented in Yangon, Myanmar.Setting Two primary care level clinics in urban Yangon, Myanmar.Design This is a feasibility study of a highly effective care model. Using Intervention Complexity Framework by Gericke et al, we collated and analysed programmatic data and evaluation data to outline key project implementation requirements and experiences.Participants Programmatic data were collected from clinical records, GeneXpert device test and maintenance reports, national guidelines, product and device instructions and site monitoring visit reports. Healthcare providers involved in delivering care model contributed interview data.Results The main feasibility considerations are appropriate storage for test kits and treatments (in response to temperature and humidity requirements), installation of a continuous stable electricity supply for the GeneXpert device, air-conditioning for the laboratory room hosting GeneXpert, access to a laboratory for pretreatment assessments and clear referral pathways for specialist consultation when required. Lessons from our project implementation experiences included the extensive time requirements for patient education, the importance of regular error monitoring and stock storage reviews and that flexible appointment scheduling and robust reminder system likely contributed to high retention in care.Conclusions Detailed documentation and dissemination of feasibility requirements and implementation considerations is vital to assist others to successfully implement a similar model of care elsewhere. We provide 10 recommendations for successful implementation.Trial registration number The trial was registered at ClinicalTrials.gov NCT03939013 on May 6, 2019. This manuscript presents post-results data on feasibility.